EFFECTIVENESS PROFILE OF AMLODIPINE AND LISINOPRIL IN HYPERTENSION OUTPATIENTS AT PRATAMA CLINIC SIDOARJO - Andri Priyoherianto; Elly Purwati; Erna Fitriany; Husna (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2023)
Hypertension is the leading cause of premature death worldwide. An estimated 1.28 billion adults aged 30-79 years worldwide have hypertension. Treatment of hypertension is usually aimed at preventing morbidity and mortality from hypertension. The choice of drugs for each patient's hypertension depends on the metabolic and subjective side effects caused. This study aims to determine the effectiveness profile of antihypertensive drugs amlodipine 10 mg or lisinopril 10 mg in outpatients at the Sidoarjo Pratama Clinic for January- March 2023. This research method is observational, with a cross-sectional approach and data collection. Quantitative analysis was then done using the statistical program SPSS 24 with univariate analysis. The results of the independent t-test showed a significance value for the systolic category of 0.780 > 0.05 and a significance value for the diastolic category of 0.931 > 0.05. Patients receiving therapy with amlodipine 10 mg or lisinopril 10 mg reached the target in 30 patients. After doing the independent t-test before and after therapy in both the systolic category and the diastolic category, it can be concluded that there is no significant difference in the effectiveness of the two groups. Keywords: Amlodipine, Blood Pressure, Hypertension, Lisinopril